2004
DOI: 10.1093/pubmed/fdh152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the introduction of fee for service payments on types of minor surgical procedures undertaken by general practitioners: observational study

Abstract: The 1990 general practitioners (GPs) contract introduced item of service payment for minor surgery, payable for six categories of procedure. Early review showed no substitution of cheaper procedures for more expensive treatments. Detailed payment data from six Health Authorities for the period 1993-2000 show an 11 per cent increase in claims, largely accounted for by the rise in cautery, incorporating cryotherapy. Cryotherapy is no more effective at treating warts than cheap commercially available products, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In our previous review, we also suggested that financial incentives introduced for GPs to conduct minor surgery in the early 1990s led to them carrying out operations for relatively trivial conditions that would not previously have been referred to hospital or where non-operative treatments were available, a conclusion supported by a more recent study. 202 A second set of studies assessed the impact of the QOF on hospital utilisation. [199][200][201]203 This pay-for-performance scheme did not (initially) have any incentives related to outpatient referrals but did provide incentives for chronic disease management that could have impacted on referrals.…”
Section: Scoping Review (Main Study)mentioning
confidence: 99%
“…In our previous review, we also suggested that financial incentives introduced for GPs to conduct minor surgery in the early 1990s led to them carrying out operations for relatively trivial conditions that would not previously have been referred to hospital or where non-operative treatments were available, a conclusion supported by a more recent study. 202 A second set of studies assessed the impact of the QOF on hospital utilisation. [199][200][201]203 This pay-for-performance scheme did not (initially) have any incentives related to outpatient referrals but did provide incentives for chronic disease management that could have impacted on referrals.…”
Section: Scoping Review (Main Study)mentioning
confidence: 99%
“…Thus, this study contends that remuneration structures in future contracts need to recognise how GPs can react to financial incentives rationally in a self-interested manner, as noted by Croxson et al (2001), Pockney et al (2004), Walley et al (2000) and Whynes et al (1999). However, these structures must also ensure that their underlying altruistic professional values and demonstrable behaviours are appropriately reflected (Hausman and Le Grand, 1999;Spoor and Munro, 2003;Young et al, 2012) and not adversely interfered with.…”
Section: Limitations and Implicationsmentioning
confidence: 96%
“…As evidence, Pockney et al (2004) identified GPs making extensive use of a surgical procedure that, although more profitable for them, is no more effective than cheaper alternatives. Walley et al (2000) found that financial incentives associated with prescribing can encourage changes in GP behaviours, while the use of 'fee-for-service' has the potential to induce demand through incentivising repeat visits and over-provision of care (Brick et al, 2012;Godager and Wiesen, 2011;Gosden et al, 2001;Green, 2014).…”
Section: Doctor Self-interest: Income-seeking Behaviourmentioning
confidence: 99%
“…4,6 It has proved satisfactory for the patient as well as enriching, complementing and granting prestige to the activity carried out by the primary care doctor.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference is that in Spain its practice does not imply an economic incentive. 4,8 The need of an initial investment in equipment and its maintenance is an essential requirement when starting a programme in minor surgery. In some cases this may be a disadvantage 7 even though expenses in surgical material in primary care result in being more cost-effective.…”
Section: Introductionmentioning
confidence: 99%